Better nurse work environments associated with fewer readmissions and shorter length of stay among adults with ischemic stroke: A cross‐sectional analysis of United States hospitals. Issue 3 (2nd March 2021) - Brom, Heather; Brooks Carthon, J. Margo; Sloane, Douglas; McHugh, Mathew; Aiken, Linda
Abstract: Stroke is among the most common reasons for disability and death. Avoiding readmissions and long lengths of stay among ischemic stroke patients has benefits for patients and health care systems alike. Although reduced readmission rates among a variety of medical patients have been associated with better nurse work environments, it is unknown how the work environment might influence readmissions and length of stay for ischemic stroke patients. Using linked data sources, we conducted a cross‐sectional analysis of 543 hospitals to evaluate the association between the nurse work environment and readmissions and length of stay for 175, 467 hospitalized adult ischemic stroke patients. We utilized logistic regression models for readmission to estimate odds ratios (OR) and zero‐truncated negative binomial models for length of stay to estimate the incident‐rate ratio (IRR). Final models accounted for hospital and patient characteristics. Seven and 30‐day readmission rates were 3.9% and 10.1% respectively and the average length of stay was 4.9 days. In hospitals with better nurse work environments ischemic stroke patients experienced lower odds of 7‐ and 30‐day readmission (7‐day OR, 0.96; 95% confidence interval [CI]: 0.93–0.99 and 30‐day OR, 0.97; 95% CI: 0.94–0.99) and lower length of stay (IRR, 0.97; 95% CI: 0.95–0.99). The work environment is a modifiable feature of hospitals that should be considered when providing comprehensive stroke care and improving post‐stroke outcomes.